HUBUNGAN ANTARA PROBLEMATIC INTERNET USE DENGAN PROKRASTINASI AKADEMIK MAHASISWA - Rian Delmar Etwiory; Doddy Hendro Wibowo (Bajang Institute, 2024)
This research aims to investigate the link between excessive internet usage and academic procrastination among students. Using purposive sampling, the researchers gathered data from a total of 107 students. The analysis employed Pearson's product moment correlation. The study utilized two scales: one measuring problematic internet use and the other measuring academic procrastination. The findings revealed a significant positive correlation (r = 0.488, p = 0.000, p < 0.05), indicating that medium levels of problematic internet use correspond to increased academic procrastination. Conversely, lower problematic internet use was associated with reduced academic procrastination. These results underscore the importance of students understanding the implications of excessive internet use to mitigate academic procrastination